(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to determine the feasibility of electronic modules developed, to determine the effect of using e-modules on increasing learning motivation and to determine the impact of using e-modules on the learning outcomes of fifth grade students of Palangka Raya City Public Elementary School. This research approach uses an R&D approach. From student learning motivation and showed an increase of 72%. E-modules also affect student learning outcomes. This research resulted in developing a new and feasible e-module for grade V elementary school students that utilizes information and communication technology in the learning process. This means that there is an effect of using e-modules on student learning outcomes in Catholic religious education. This research contributes to the field of education by developing innovative learning tools, increasing student learning motivation, and proving the effectiveness of using E-modules in improving student learning outcomes in Catholic Religious Education subjects.